Amok School Shooting und zielgerichtete Gewalt - Huck, Wilfried (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2011)
In the child and adolescent psychiatric clinics, more and more children and adolescents are being introduced by schools, school psychology services, youth welfare offices and the police in order to have their potential risks assessed professionally. Against this background, but also in view of the dramatic rampage events in Erfurt, Emsdetten and Winnenden, the book provides an overview of the latest interdisciplinary research findings as well as attempts to explain the specific dynamics and conveys treatment concepts and approaches to prevention. The author pursues the principle that only an interdisciplinary approach and the synopsis of the various aspects from a developmental psychological, depth psychological, systemic, neurobiological and sociological perspective can do justice to the complex topic of understanding the dynamics.